Thermal stability and behaviour of paraffin nano Al2O3, graphene and surfactant sodium oleate composite as phase change material. (1st November 2022) - Prabhu, S Selva; Selvakumar, P; Heric, J S
Abstract: Organic phase change materials like paraffin possess high latent heat yet incredibly low thermal conductivity. For improving the thermal conductivity, nanomaterials are introduced into the phase change materials. Thermal energy storage applications benefit from the use of phase transition materials with high thermal conductivity and latent heat of fusion. In this work to increase the dispersion of the alumina and graphene nanoparticles, a novel nanocomposite phase change material was produced by utilizing sodium oleate as a surfactant. The surfactant sodium oleate is prepared with oleic acid and methanol, The mixture is prepared using sodium oleate, Alumina Nanoparticle, and Graphene in the mass ratio of 1:3:0.5 is mixed with paraffin in the weight percentage of 7.5 and 10 and thermal stability study was carried out. Alumina nanoparticles were synthesized and prepared by using a microwave-assisted chemical precipitation approach which is more effective and graphene nanoparticles were prepared by using modified hummer's method. Thermocycling was used for up to 100 cycles to determine the melting point, latent heat, and long-term thermal stability of nanocomposites with phase change material. Differential Scanning Calorimetry (DSC) was used to evaluate the heat storage behaviour of the samples, and the heating rate of nanocomposites containing PCMs was investigated. The transient hot wire method was then utilised to assess the PCM's actual thermal conductivity. From the obtained results, nanocomposite with 7.5 wt% additives show maximum thermal stability and latent heat (161.09 KJ Kg −1 ) for 100 cycles with an increase in 42% effective thermal conductivity, Nanocomposite with 10 wt% shows 57% higher thermal conductivity. But shows lower thermal stability and very low latent heat (120.44 KJ Kg −1 ). It is understood from the results that nanoparticle and surfactant addition gives a positive rise in latent heat.